PERANCANGAN SISTEM INFORMASI PENJUALAN FURNITURE BERBASIS WEB PADA PK. BUMI JAYA BEKASI - Saryoko, Andi (www.bsi.ac.id, 2015)
Today's modern era, the development of information technology goes so rapidly. The need for a technology is needed. One of them is the internet being used to obtain information in a short time. In many internet consumers who are looking for particular items of furniture, where consumers can obtain information and facilitate in pemesana and purchasing furniture. PK. Bumi Jaya is one company that is engaged in the manufacture and sale of furniture. The program is to be taken about the design of the website selling the PK. Bumi Jaya. Where this program is designed to simplify the booking and purchase of furniture for the consumer. The author makes writing material obtained from interviews with the PK. Bumi Jaya, observation and library reference books related to ordering and buying from the internet. Here the authors chose a program with application software Macromedia Dreamweaver 8 for database using PHP and MySQL. Due to its simplicity to create a dynamic website. Keywords: Information System Design, Furniture Sales, Web-Based